2009
DOI: 10.1016/j.vetmic.2008.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR for identification of Brucella spp.: A comparative study of IS711, bcsp31 and per target genes

Abstract: Culture is considered as the reference standard assay for diagnosis of Brucella spp. in humans and animals but it is time-consuming and hazardous. In this study, we evaluated the performances of newly designed real-time PCR assays using TaqMan probes and targeting the 3 following specific genes: (i) the insertion sequence IS711, (ii) bcsp31 and (iii) per genes for the detection of Brucella at genus level. The real-time PCR assays were compared to previously described conventional PCR assays targeting the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
2
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(128 citation statements)
references
References 33 publications
2
109
2
15
Order By: Relevance
“…It is noteworthy that different copy numbers of IS711 in various species and biovars affect the accuracy of the bacterial load estimation by real-time PCR assays that target this fragment, particularly in culture-negative cases. Bounaadja et al reported that the C T differences between IS711 and bcsp31 (⌬C T IS/bcsp) were 0.18 to 2.35 and 0.41 to 2.50 for the same B. abortus and B. melitensis DNA loads, respectively (31). Hence, the bcsp31 with one copy in brucellae can serve as an exact indicator for the detection of Brucella spp.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that different copy numbers of IS711 in various species and biovars affect the accuracy of the bacterial load estimation by real-time PCR assays that target this fragment, particularly in culture-negative cases. Bounaadja et al reported that the C T differences between IS711 and bcsp31 (⌬C T IS/bcsp) were 0.18 to 2.35 and 0.41 to 2.50 for the same B. abortus and B. melitensis DNA loads, respectively (31). Hence, the bcsp31 with one copy in brucellae can serve as an exact indicator for the detection of Brucella spp.…”
Section: Discussionmentioning
confidence: 99%
“…(Navarro et al, 2004). The BCSP31-PCR assay was carried out using standard procedure (Baily et al, 1992;Bounaadja et al, 2009), and IS711-PCR was done using the procedure described by Halling et al (1993). The cut off for the cycle threshold (Ct) values of real-time PCR positivity is 40.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…However, sensitivity of the omp2a LAMP assay was equivalent to TaqMan probe based real time PCR. The IS711 TaqMan probe based real time PCR has been reported as a highly sensitive method in detecting less than 10 fg of genomic DNA (three genome copies) of Brucella organisms [17,23,24].…”
Section: Resultsmentioning
confidence: 99%